China’s expansion into the Western Hemisphere : implications for Latin America and the United States, por Riordan Roett y Guadalupe Paz (eds.), Washington : Brookings Institution Press, 2008 - Soto Alvarez, Augusto (Estudios Internacionales, 2008)
-